Perbandingan Kepuasan Pelanggan Terhadap 3 Brand Minuman Kekinian di Medan - Erickho Chandra; Ester Fanny Nagatan; Fendy Wangsa; Leo Kendrew; Valencia Taifanny (Institut Nalanda, 2024)
The main objective of this study was to determine the satisfaction comparison between 3 contemporary beverage brands in Medan. This research falls into the category of quantitative research. The study population consisted of consumers of the contemporary beverage brands TOMORO, KOPI KENANGAN and STARBUCKS in Medan city, and a sample of 30 respondents was selected using the simple random sampling method. Data collection was carried out using a questionnaire via google form. From the analysis, it was found that the KOPI KENANGAN beverage brand has a higher level of satisfaction compared to the TOMORO and STARBUCKS beverage brands. This is due to affordable prices, large product variations and good product quality.